Uji Ekstrak Etanol Kulit Nanas (Ananas comosus L.) sebagai Antibakteri - Yolandari, Sri; Tasjiddin Teheni, Muhammad; Wulandari, Musriati (Politeknik Baubau, 2022)
This study aims to determine the inhibitory activity of the ethanolic extract of pineapple peel (Ananas comosus L.) from Staphylococcus aureus bacteria and to determine the antibacterial effect of the ethanolic extract of pineapple peel (Ananas comosus L.) on the growth of Staphylococcus aureus bacteria. This study uses the maceration method. Based on the results of the study, . Concentrations used were 10%, 30% dan 50% with inhibition 10% = 7,167 mm, 30% = 13,167 mm and 50% = 14,83 mm. It can be concluded that the ethanolic extract of pineapple peel (Ananas comosus L.) has an antibacterial effect and can inhibit antibacterial activity against Staphylococcus aureus bacteria